2015
DOI: 10.4103/0971-9784.154478
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine in adult cardiac surgery and the cardiac surgery Intensive Care Unit: An evidence-based clinical review

Abstract: Ketamine is a unique anesthetic drug that provides analgesia, hypnosis, and amnesia with minimal respiratory and cardiovascular depression. Because of its sympathomimetic properties it would seem to be an excellent choice for patients with depressed ventricular function in cardiac surgery. However, its use has not gained widespread acceptance in adult cardiac surgery patients, perhaps due to its perceived negative psychotropic effects. Despite this limitation, it is receiving renewed interest in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 46 publications
1
19
0
1
Order By: Relevance
“…[79][80][81] The use of ketamine in cardiac surgery was associated with decreased inflammation, opioid sparing, and improved patient satisfaction postoperatively. [82][83][84][85][86][87][88][89][90] Its use in the prevention of chronic poststernotomy pain has not been studied.…”
Section: Acetaminophenmentioning
confidence: 99%
“…[79][80][81] The use of ketamine in cardiac surgery was associated with decreased inflammation, opioid sparing, and improved patient satisfaction postoperatively. [82][83][84][85][86][87][88][89][90] Its use in the prevention of chronic poststernotomy pain has not been studied.…”
Section: Acetaminophenmentioning
confidence: 99%
“…[ 7 8 9 ] In cardiac surgery and the cardiac Intensive Care Unit (ICU), only one review has focused specifically on ketamine, without truly addressing its use for pain management. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Mogahad MM etal had compared safety and efficacy of ketaminedexmedetomidine (KD) versus ketamine-propofol (KP) combinations for sedation in patients after coronary artery bypass graft surgery and concluded that KD provided short duration of mechanical ventilation with less fentanyl dose requirement in comparison with KP whereas hemodynamic stability and length of the ICU stay was same with both the regimens [76]. Future studies comparing ketamine to other commonly accepted sedative regiments, such as propofol and dexmedetomidine are critically needed in cardiac surgery patients [77]. Some authors have reported that a single dose of ketamine 0.5 mg/kg given upon induction was associated with lower serum levels of C-reactive protein and lower incidence of delirium and cognitive dysfunction after cardiac surgery with CPB.…”
Section: Some Other Clinical Uses Of Ketamine Available In Literaturementioning
confidence: 99%